Effects of heavy metals (Cd, Cu, Pb, Hg) on pollen germination and tube growth of quince (Cydonia oblonga M.) and plum (Prunus domestica L.) - Gür, Nazmi; Topdemir, Aykut (My University, 2005)
Pollen germination and tube elongation rate have fre-quently been used as indicators for air pollution with heavy metals. The tubes of quince and plum pollen were germi¬nated in a culture medium containing the heavy metals Cd, Cu, Hg and Pb. According to the results obtained, these heavy metals led to a significant decrease in pollen germi¬nation and tube growth. It was found that there was a paral¬lelism between the concentration of heavy metal salts, and pollen germination and tube growth. While Cd had the most inhibiting effect on pollen germination and tube growth of plums, Cu had the least. Mercury showed the highest toxicity, whereas pollen germination and tube growth rate was less affected by copper in quince plants. As a result, all heavy metals examined negatively affected pollen germination and tube growth in quince and plum plants, but their toxicity levels varied.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pollen germination; Pollen tube growth; Heavy metals; Quince; Plum